Human platelet lysate-derived exosomes are superior to the lysate at increasing collagen deposition in a rat model of intrinsic aging - Ervina Rosmarwati, Endra Yustin Ellistasari, Arie Kusumawardani, Indah Julianto, Suci Widhiati, Novan Adi Setyawan, Frieda Yanuar (Journal of Applied Pharmaceutical Science, 2023)
The decreased production of collagen in intrinsic aging skin is most likely due to the downregulation of connective tissue growth factor (GF) which is thought to be a regulator of collagen expression. Human platelet lysate (HPL) contains many nutrients needed for cell growth and proliferation. The GFs are contained not right in liquid lysate but in exosomes. Our study demonstrated the superiority of Exo-HPL compared to HPL in decreasing matrix metalloproteinase (MMP)-1 level and increasing collagen deposition in intrinsic aging rat models (IRMs) induced by injection of D-galactose. The highest deposition of collagen at 40× magnification is found in IRM + Exo-HPL treatment group (38.40%) which is close to collagen deposition in the young rats group (42.90%). At 100× magnification the study demonstrated that there was higher collagen deposition in IRM + Exo-HPL treatment group (39.94%) than in IRM + HPL treatment group (34.53%) which was close to the young rat group’s collagen deposition (43.26%). This study found a significant difference in MMP-1 level and collagen deposition among all groups. Both Exo-HPL and HPL treatment groups decreased MMP-1 levels and increased collagen deposition compared to IRM group. Exo-HPL treatment group was more effective in decreasing MMP-1 level and increasing collagen deposition compared to HPL treatment group and IRM group significantly.
Keywords: Collagen, D-Gal, Exo-HPL, HPL, intrinsic aging, MMP-1